Study on Impact of Iron and Folic Acid on the Plasma Trace Minerals in Pregnant Anemic Women - Tiwari, Amit Kumar Mani (Indian J Clin Biochem, 2017)
Iron deficiency anemia is one of the causes that lead to significant mortality and morbidity among pregnant women and fetus. The present study was undertaken to explore oral iron supplementation can modify the metal contents in pregnant anemic women. Iron and folic acid supplementations was given to 500 anemic women (mild = 200, moderate = 200, and severe = 100) and 100 age matched non-anemic controls daily for 100 days. Blood index values and plasma trace minerals were estimated as per standard protocols. Haemoglobin and ferritin levels were found significantly increased (p < 0.001) in anemic and control subjects after treatment. Moreover, the serum transferring receptor levels and total iron binding capacity were found significantly decreased in all treated groups. Iron (Fe), zinc (Zn) and copper (Cu) levels were found increased (p < 0.01) after oral iron supplementation groups. Moreover, selenium (Se) manganese (Mn) and were found to be decreased in all treated groups. Data provides the conclusion that iron and folic acid supplementation recovered the essential trace minerals, except manganese, which may lead to various complications including peroxidation of vital body molecules resulting in increased risk for pregnant women as well as fetus.